Quantitative PCR (qPCR) assay for the specific detection of the Chinese mystery snail (Cipangopaludina chinensis) in the UK. - Helen C Rees; Gavin H Measures; Steven D Kane; Ben C Maddison (PLoS ONE, 2023)
Cipangopaludina chinensis Gray 1833 is an East Asian freshwater snail and invasive species in many parts of the world (Global Invasive Species Database, 2022). Within the UK, it was first found at the Pevensey Levels, Sussex, and has since been reported at a second site at Southampton Common, Hampshire. Both sites are designated as Sites of Special Scientific Interest (SSSI) for their wildlife importance. Although the impacts of this species within the UK have not yet been investigated several exotic parasites of the snail have been reported and research suggests that its presence can negatively impact native snail species. This is especially important at the Pevensey Levels due to the presence of the rare freshwater mollusc Anisus vorticulus (Little Whirlpool Rams's-horn snail). Here, we have developed a qPCR-based eDNA assay for the detection of C. chinensis and compared water samples tested for eDNA with results from manual survey of the ditches at the Pevensey Levels. Our eDNA analysis exhibited an overall observed percentage agreement of 80% with a kappa coefficient of agreement between manual and eDNA surveys of 0.59 (95% CI 0.31 to 0.88). Some samples which were qPCR negative for C. chinensis were positive by manual survey, and vice versa revealing the potential for improved overall detection rates when using a combination of manual and eDNA methodologies. eDNA analysis can therefore augment manual survey techniques for C. chinensis as a relatively quick and inexpensive tool for collecting presence and distribution data that could be used to inform further manual surveys and control measures within the ditches.